2009
DOI: 10.1097/aog.0b013e3181b5cba3
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome After Treatment for Cervical Intraepithelial Neoplasia

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 30 publications
(37 reference statements)
1
44
1
3
Order By: Relevance
“…When studies examining preterm birth subtypes; preterm prelabour rupture of membranes (pPROM) and spontaneous preterm birth were analysed, the pattern for spontaneous preterm birth, with a pooled relative risk of 1.99 (95% CI 1.68-2.36), 11,13,26,36,38 was similar to that of all preterm birth using an external comparison group. The estimate for the risk of preterm prelabour rupture of membranes was higher, with a wider confidence interval (pooled RR 3.40, 95% CI 1.63-8.11).…”
Section: Association Of Excisional Methods Of Treatment and Preterm Bmentioning
confidence: 99%
See 1 more Smart Citation
“…When studies examining preterm birth subtypes; preterm prelabour rupture of membranes (pPROM) and spontaneous preterm birth were analysed, the pattern for spontaneous preterm birth, with a pooled relative risk of 1.99 (95% CI 1.68-2.36), 11,13,26,36,38 was similar to that of all preterm birth using an external comparison group. The estimate for the risk of preterm prelabour rupture of membranes was higher, with a wider confidence interval (pooled RR 3.40, 95% CI 1.63-8.11).…”
Section: Association Of Excisional Methods Of Treatment and Preterm Bmentioning
confidence: 99%
“…4 In addition, a systematic review (without meta-analysis) was published in 2007. 5 A number of large studies [6][7][8][9][10][11][12][13][14] examining this question have been published since the most recent review, 3 making it timely to update the analysis and examine methodological issues that may influence the findings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous studies have reported that excised cone size [8,13], number of cervical excisions [8], cervical length at 22-24 weeks of gestation [20,24], and the time interval between surgery and pregnancy [25] are factors that might increase the risk of preterm delivery among women who have previously undergone LEEP. Excision treatments of the transition zone depend on the nature and the extent of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…An early report showed that there is an association between cold-knife conization and adverse obstetric outcomes, including preterm delivery [5]. Subsequently, several systematic reviews and large retrospective studies have reported that women who have undergone LEEP have a 1.7-3.7-fold increased risk of preterm delivery, low birth weight, and premature rupture of the membrane compared with untreated women [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing body of evidence that tissue excision is associated with preterm labour, some observational studies have suggested an increased risk of preterm birth associated with CIN itself, regardless of treatment. [11][12][13][14] This association has been attributed to the fact that some women are at high risk of both CIN and preterm birth, or that both conditions are mediated by a common process, such as infection. Prospective studies are required to fully assess the relationship between pre-invasive cervical disease, its treatment and obstetric outcomes.…”
mentioning
confidence: 99%